2017
DOI: 10.1007/s11948-017-9913-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Chinese Biomedical Researchers Towards Academic Misconduct: A Comparison Between 2015 and 2010

Abstract: Publications by Chinese researchers in scientific journals have dramatically increased over the past decade; however, academic misconduct also becomes more prevalent in the country. The aim of this prospective study was to understand the perceptions of Chinese biomedical researchers towards academic misconduct and the trend from 2010 to 2015. A questionnaire comprising 10 questions was designed and then validated by ten biomedical researchers in China. In the years 2010 and 2015, respectively, the questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Here, a combination of the 'publish or perish' syndrome, payment for publication in WoS journals, and an in-built respect for authority figures in China mean that it is common for new, or less qualified, staff to include better established, senior colleagues as authors in an attempt to increase the chance that a submission will be accepted for publication in a prestigious journal. It must be emphasised that we are not suggesting that this is a purely Chinese phenomenon since it clearly occurs in many countries and disciplines (Sokol, 2008;Strange, 2008;Zaki, 2011); however, it is known to be particularly well established in the Chinese context (Hvistendahl, 2013;Liao et al, 2017;Macfarlane, 2017). For example, an empirical analysis by Hao et al (2009) found that guest authorship was involved in 28.6% of papers published in 2008 in the Chinese Medical Journal, the great majority of the guest authors being heads of departments or institutions.…”
Section: Discussionmentioning
confidence: 82%
“…Here, a combination of the 'publish or perish' syndrome, payment for publication in WoS journals, and an in-built respect for authority figures in China mean that it is common for new, or less qualified, staff to include better established, senior colleagues as authors in an attempt to increase the chance that a submission will be accepted for publication in a prestigious journal. It must be emphasised that we are not suggesting that this is a purely Chinese phenomenon since it clearly occurs in many countries and disciplines (Sokol, 2008;Strange, 2008;Zaki, 2011); however, it is known to be particularly well established in the Chinese context (Hvistendahl, 2013;Liao et al, 2017;Macfarlane, 2017). For example, an empirical analysis by Hao et al (2009) found that guest authorship was involved in 28.6% of papers published in 2008 in the Chinese Medical Journal, the great majority of the guest authors being heads of departments or institutions.…”
Section: Discussionmentioning
confidence: 82%
“…These retracted meta-analyses were concentrated in a small number of journals, especially Tumor Biology and Molecular Biology Reports. It has been suggested that an irrational scienti c evaluation system may be partly blame for this misconduct (Chen et al 2018;Wang et al 2018;Liao et al 2018). Chinese researches have been pressured heavily to publish articles in Web of Science-indexed journals to achieve promotion and funding (Liao et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the measure that seems to solve the problem fundamentally, but it is actually impossible to be promoted by individual hospitals: reform the doctor evaluation system, there are some short-term and mild measures that can be taken. In a prospective study on perceptions of Chinese Biomedical researchers towards research misconduct among Chinese biomedical researchers, more than 60% of participants thought that the punishment for research misconduct from authority and institutions was not severe enough (12). In fact, few hospitals in China have detailed rules and enforce them transparently, putting researchers with retracted publications at a disadvantage to their long-term interests, such as relegation, be limited to access to academic resources, and no promotion for several years (33).…”
Section: Resultsmentioning
confidence: 99%
“…These may cause difficulties in maintaining original records, difficulties in monitoring the research process by the corresponding author, and motivating doctors to find other solutions. Hospitals have a positive attitude towards acknowledging their articles, but have a negative attitude towards accountability for research misconduct(12). Doctors in China need to publish papers in academic journals for promotion and economic benefits.…”
mentioning
confidence: 99%